Analisis Praanggapan Pada Channel Youtobe Podcast Deddy Corbuzier Bersama Novel Baswedan - Dira Elfitri (Universitas Cokroaminoto Palopo, 2021)
Presuppositions have an important role in the ongoing communication process, because a communication can be well established if the speaker and the interlocutor have the same presuppositions or assumptions about what they are talking about. The similarity of assumptions can be influenced by contexts outside the language, such as cultural, social, age, and other backgrounds. This is the background for the researcher entitled Presupposition Analysis on the YouTube Podcast Channel Deddy Corbuzier with Novel Baswedan. The problem in this study is how the types of presuppositions contained in Deddy Corbuzier's podcast with Novel Baswedan. This study aims to identify and describe the types of presuppositions contained in Deddy Corbuzier's podcast with Novel Baswedan. The approach used in this research is a qualitative approach using content analysis method. The data collection techniques used by researchers in this study were documentation techniques, listening techniques, and note-taking techniques. The results of this study indicate that there are 66 utterances containing presuppositions in the conversation between Deddy Corbuzier and Novel Baswedan. The 66 utterances are then grouped according to the type of presupposition according to the theory put forward by Yule. Found 16 utterances belonging to existential presuppositions, 9 lexical presuppositions, 25 structural presuppositions, 6 factive presuppositions, 9 non-factual presuppositions, and 1 counterfactual presupposition. Structural presuppositions are most often found because the object of research is in the form of speeches in podcasts that are seeking information and classifying things by asking questions.